Indonesian Language Acquisition of 0-2-Year-Old Children: A Study of Psycholinguistic Perspective - Anum, Adelina; Susanti, Ratna; Syakur, Abd. (Journal Corner of Education, Linguistics, and Literature, 2024)
This study discusses the problem of phonology and morphology acquisition in children aged 0-2 years whose parents use Indonesian in their daily interaction (communication) in the family while the surrounding community interacts (communicates) using the local language (Javanese). This research concludes that the embryonic development of children's language can vary in each individual, can develop quickly and can also be slow, depending on the level or level of age, the ability of the parents, and the active environment to develop it. This type of research is descriptive qualitative research. The data generated from this research is in the form of spoken words, which will then be transcribed into writing. Data related to this research, which is devoted to language acquisition in the form of phonology and morphology acquisition in children aged 0-2 years, was obtained using several methods.